PEMBEKALAN SISWA DALAM MENGHADAPI DUNIA KERJA - Muhamad Ekhsan; Yuan Badrianto; Siti Juariah; Dwi Astuti; Nataliana Bebasari (Abdi Jurnal Publikasi, 2022)
This service activity aims to initiate a preparation program for the world of work for generation Z which is specifically held at the Bina Industri Vocational School in Cikarang, where the location of this Vocational School is right behind the capital-intensive industrial area in Bekasi. The purpose of this debriefing for Industrial Bina Vocational High School students is an empowerment effort in forming individual and community characters that are more independent and competitive. This student independence is defined as a condition experienced by students consciously building self-competence, deciding and doing the right thing in competing in the world of work that will be faced by preparing adequate skills. This debriefing provides some important understanding of the preparation for the world of work, awareness of building competence and knowledge of culture, especially in large companies located in the MM2100 area, Vocational School students on duty get several other benefits from increasing competence.